Building school leaders’ instructional leadership capacity through virtual professional leadership learning communities - Pashmforoosh, Roya; Irby, Beverly J.; Lara-Alecio, Rafael; Tong, Fuhui (Frontiers in Education, 2023)
Research is still emerging on how to develop school leaders’ instructional capacity. We implemented research-based practices through virtual professional leadership learning communities (VPLCs) for building school leaders’ instructional capacity. We examined school leaders’ perceptions of (a) the effectiveness of the VPLC as a vehicle for improving instructional practices, (b) the essential components of an effective VPLC, and (c) school leaders’ instructional leadership practices through discussions within VPLC. We indicated that practicing school leaders were positive toward the VPLC in terms of (a) increasing convenience and professional networking, (b) supporting community building and critical reflection among school leaders, and (c) providing resources for future use. These VPLCs were regarded as grounds for innovation, as participants worked together with other school leaders to find problems and determine creative and workable solutions focused on building instructional capacity in serving high-needs schools. Thus, we can better support our nation’s school leaders through sustained, effective professional learning in communities of practice.